Analisis Pengembangan Pariwisata Di Kabupaten Pulau Morotai - rahmawati, dini (Lembaga Pengembangan Kinerja Dosen, 2024)
In Indonesia, tourism still has an important role in supporting national development. Morotai Island as a border area has a huge local potential in mining, farming, plantation, including human resources and tourism. Therefore, this research aimed to provide a recommendation for tourism development and so that to improve tourism competitiveness, particularly tourism activity conducted by tourists, based on SWOT analysis. This research used descriptive qualitative method. The research location was in the territory of Daruba, South Morotai, Morotai Island District, North Maluku Province. The data were obtained by doing observation, interview and literature study. In the interview part, some staff of Tourism Board and local people became the sources through focus group discussion and direct interview referred to purposive sampling technique. The SWOT analysis shows that Morotai Island District has nature beauty and War World II historical ruins as the strength. Those still have a huge opportunity to develop so that to revive the tourist activity there. Not to mention, Kelapa Bido as an endemic plant in Morotai Island District. Based on the SWOT analysis and observation, the recommendations for tourism activity are managing tour packages, agrotourism and digital tourism via augmented and virtual reality.